Mechanical properties of tin slag filled polyester composites / Muhamad Rezza Abdul Manaf ... [et al.] - Abdul Manaf, Muhamad Rezza; Mohamed Hashim, Siti Raihana; Kamarudin, Surianajiha; Rashidi, Ahmad Ramli (2018)
The mixture of tin slag (TS) powder and polyester (PE) along with Methyl Ethyl Ketone Peroxide (MEKP) as the catalyst were studied in this paper. This study is about the properties of PE alone and the addition of TS as the filler. Three formulations are prepared which are 5 wt%, 10 wt% and 15 wt%. The MEKP is used to harden the mixture. The objective of this study to determine the mechanical properties of the mixture. The samples obtained are tested with two different types of testing which are tensile and flexural. As the wt% increases it will cause the mixture of TS and PE result in a poor structure rather than PE alone. The 5% of addition gives the best results in the flexural testing and the pure PE has better tensile properties compared to the other formulations.